Pengaruh Penyuluhan Tentang Gizi 1000 Hari Pertama Kehidupan Ibu Hamil terhadap Pengetahuan, Sikap dan Tindakan untuk Mencegah Stunting: The Effect of Nutrition Education on the First 1000 Days of Life for Pregnant Women on Knowledge, Attitudes, and Practices to Prevent Stunting - Simamora, Debora Natalia; Simbolon, Oknalita; Debataraja, Fransiska; Simamora, Mayes Felda (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Nutrition during the First 1000 Days of Life (HPK), starting from pregnancy to the child’s second birthday, is a critical period that determines the quality of a child’s growth and development. Low maternal knowledge regarding 1000 HPK nutrition is one of the main factors contributing to the risk of stunting in children. This study aims to analyze the effect of nutrition education on improving the knowledge, attitudes, and practices (KAP) of pregnant women in preventing stunting in the working area of Matiti Community Health Center, Humbang Hasundutan Regency. This study employed a quasi-experimental design with a pre-test and post-test control group approach. The population consisted of 149 pregnant women, with a total sample of 60 participants divided into intervention and control groups using purposive sampling. The intervention was delivered through lectures and poster media over a two-week period. The variables measured were knowledge, attitudes, and practices of pregnant women. A standardized questionnaire was used, and data were analyzed using the Paired Samples Test. The results showed a significant improvement in the intervention group after the education session, with the mean knowledge score increasing from 10.83 to 15.93 (p = 0.000), attitude from 21.06 to 33.10 (p = 0.000), and practices from 4.36 to 8.93 (p = 0.000). In contrast, the control group showed no significant changes. The education intervention using lectures and posters proved effective in enhancing pregnant women’s nutritional behavior. It can be concluded that 1000 HPK nutrition education significantly improves the knowledge, attitudes, and practices of pregnant women. It is recommended that such educational programs be widely implemented by healthcare workers as a strategic effort to prevent stunting, especially in areas with high prevalence.